1967
DOI: 10.1128/jvi.1.4.717-722.1967
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of Viral Functions in Bacteriophage α

Abstract: Temperature-sensitive mutants of phage a were subjected to short pulses of permissive temperature at various times during the lytic cycle. All the mutants showed an optimal response to the permissive pulse at a specific time after infection. The optimal responses of the mutants belonging to the same complementation group fell close together in the same time interval; the optimal responses of mutants contained in 20 different complementation groups were more or less uniformly scattered throughout the lytic cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1970
1970
1979
1979

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…Table 1 gives a list of the 25 complementation groups, the total number of mutants which was assigned to each group, and the number of mutants produced in each cistron by the different mutagens. This classification differs slightly from the one already presented by Gaeta et al (20) on the basis of earlier complementation work performed on 69 of the mutants obtained with HA. One class, XX, has been deleted since later results showed that the previous assignment of a mutant to this class was the result of highly efficient intracistronic complementation.…”
Section: Resultscontrasting
confidence: 87%
“…Table 1 gives a list of the 25 complementation groups, the total number of mutants which was assigned to each group, and the number of mutants produced in each cistron by the different mutagens. This classification differs slightly from the one already presented by Gaeta et al (20) on the basis of earlier complementation work performed on 69 of the mutants obtained with HA. One class, XX, has been deleted since later results showed that the previous assignment of a mutant to this class was the result of highly efficient intracistronic complementation.…”
Section: Resultscontrasting
confidence: 87%